The food revolution : how your diet can help save your life and our world - Robbins, John (Conari Press, 2011)
In this updated edition of the 2001 classic, Robbins details how much has changed over the past decade, with more of us turning toward plant-based diets. But abuses and hazards remain, and he issues a new call to arms, urging us toward a more sustainable, compassionate world.